Characteristics of NOx Formation and Removal in the Transient Process of a 660 MW Coal-fired Power Unit - Jiang FAN; Shuangping ZHANG; Yu MENG; Weixiong CHEN; Junjie YAN (发电技术)
In order to complete the peak load regulating of power system, coal-fired power units have long-term frequent load fluctuations, which have a significant impact on the formation and removal of nitrogen oxides. In this paper, with the goal of studying the characteristics of nitrogen oxide generation and removal in the transient process of a 660 MW coal-fired unit, a prediction model of nitrogen oxides generation in the transient process was established, and the nitrogen oxides generation prediction study in the process of variable load was carried out. According to the characteristics of the burner switching in the variable load process of the coal-fired unit, it was found that the higher load point of the newly added burner, the more effectively it can avoid the increase of the generation value of nitrogen oxides. In addition, the dynamic characteristics of selective catalytic reduction (SCR) were analyzed, and the effects of the step changes such as nitrogen oxide concentration, NH3 injection concentration, flue gas flow rate and reaction temperature on the dynamic characteristics of nitrogen oxides removal were studied respectively, which provides a reference for the optimization control logic of NH3 injection in the subsequent transient process.